Grain dust and respiratory health in South African milling workers. Issue 10 (October 1991) - Bachmann, M; Myers, J E
Abstract : Respiratory health was investigated in 224 grain milling workers. The likelihood of respiratory symptoms and chronic airflow limitation was raised for workers exposed to dust independent of the effects of smoking. Smokers were more likely than non-smokers to respond to a bronchodilator at the end of the working week. Dust was more strongly associated with most abnormal outcomes than was smoking. Subjective categories of exposure to dust were more strongly associated with most abnormal outcomes than were objective categories. The prevalence of all symptoms at the time of a survey conducted at the mill six years before was higher in workers who subsequently left the mill than in those who remained employed although the differences were not significant.